Садиби-двори рядових мешканців Копиревого кінця - Козловський, А.О.; Крижановський, В.О. (Археологія і давня історія України, 2021)
Статтю присвячено дослідженню споруд різноманітного призначення, які входили до складу давньоруських садиб-дворів, виявлених під час археологічних розкопок на території Копиревого кінця у місті Києві. On the territory of ancient Kyiv from the end of the X century are fixed numerous farmsteads and separate mansions, which belonged to princes, boyars, merchants, artisans and ordinary inhabitants, formed separate residential and economic complexes, which included both residential and various outbuildings, usually surrounded by fence. Some of the farmsteads located outside the city fortifications had their own fortifications. After analyzing the features of the ancient Rus’ buildings of the Kopyrev kinec’, the following became clear. Construction of this area begins with the construction of a fortified farmsteads at its highest point — on the street Sichovyh Striltsiv, 12 (beginning of the XI century). After that, down the slope — on the land on the street Kudriavska, 24A there is a significant number of production facilities that served the needs of the inhabitants of the boyar farmstead. Ferrous iron smelting and processing were carried out here, there were facilities for drying sheaves, a smokehouse, as well as a tar pit. At the next stage, most flammable industries disappear in the middle of the XI — first half of the XII century and in this area there are separate farmsteads of ordinary inhabitants, whose main occupation was a variety of crafts: iron processing, bronze casting, making various things from bronze, possibly making jewelry. The richest was the farmstead «Б», which had an area of up to 1200 m2 and was protected on all sides by a fence in the form of a strong fence. There were up to 20 residential, industrial and outbuildings in its area. In the central dwelling of this farmstead they were not engaged in handicrafts, but around it there was a considerable quantity of industrial premises. Most likely, this farmstead was owned by either a merchant or a fairly wealthy artisan. Farmstead «B» was smaller in size: ≈1000 m2. About 20 objects were recorded on it. Here they were engaged in smelting and processing of bronze, as well as the manufacture of various iron products. The manufacture of bronze and iron products was carried out in the central living space, and the smelting of bronze — at some distance from the living area. This farmstead could belong to a middle-class artisan who probably participated in the production processes. The smallest and poorest was the farmstead «A». Its area was about 800 m2. Here lived an artisan, who most likely engaged in smelting and processing of bronze products, most likely — in a special workshop, which was located next to the house. In addition, on the territory of modern Lvivs’ka Square there was a farmstead with a central building of log construction, around which there were outbuildings. Pottery and metalworking workshops could function here. Thus, the probable sequence of settlement of the territory of the Kopyrev kinec’ from chaotically located flammable productions to house-building was traced. The inhabitants of the farmsteads were quite clearly divided by property status, but in all estates the main occupation was handicraft.